Analyzing BSNL's Financial Inclusion Strategy - Dr. Raj Bihari Lal Srivastava (International Journal of Engineering and Management Research, 2020)
Since India is the second-largest telecommunications market in the world, the telecom industry is vital to the country's economy. BSNL is the largest telecom firm in India and is wholly owned by the government, making it an uphill battle for the corporation in recent years. A comprehensive resuscitation package for BSNL was launched by the government in 2019 in an effort to save the company from the severe financial crisis it was experiencing. The purpose of this research is to examine BSNL's financial statements for the years 2018 through 2019 in order to calculate the ROI of the company's revival package. Companies' financial statements (income statement and balance sheet) are summaries of financial reports that present the operating results and financial position of the companies, and the information contained therein is valuable for evaluating the effectiveness of the company's operations and the health of its finances. In order to do so, a number of methods (tools) have been developed by financial specialists to aid in the study and interpretation of such data. In this study, we used the Comparative Tool to compare BSNL's Financial Inclusion before and after it implemented its revival package, and we concluded that while the company's expenses have decreased by nearly half, its revenues have continued to fall—a trend we attribute primarily to the fact that its 4G services are not yet available across the country. After a long period of significant failure, it was determined that the Revival Package provided by the Government of India to BSNL had positive results, and that these results would improve if the remaining Revival Package projects were also completed as soon as possible.